Financial Centres' Polyarchy and Competitiveness Does Political Participation Change a Financial Centre's Competitiveness? - Bryane Michael; Bertrand Candelon (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2018)
What role does polyarchy (and thus increased democracy) play in aiding the development of an international financial centre? We find support for decades of theorising that some jurisdictions use autocracy (less polyarchy) to help grow out their financial centres. We look at the growth of these financial centres as the extent to which they attract more funds from abroad (cross-border bank liabilities). Polyarchy decreases as other international financial centres' centrality in the global financial centre network expands. Polyarchy increases in most jurisdictions over time because some financial centres rely on increasingly polyartic governance as a way to foster financial innovation through increased participation by non-previously powerful sectors. Namely, the growth of an international financial centre's centrality in global financial networks relies on tapping down on polyarchy. Yet, such polyarchy – when used by some very central jurisdictions to remain central – “spreads.” We model such a relationship between polyarchy and centrality in the global financial network, describing even the most complex quantitative analysis in a way a non-specialist can understand. These results could impact decisions ranging from Brexit to Hong Kong's autonomy in its post-2047 period.
Keywords: D72; F55; F33; P48; 330; international financial centres; endogenous global city network centrality; dynamic polyarchy; Bayesian network analysis